Cognitive and behavioral assessment in Parkinson's disease. (3rd July 2019) - Martinez-Horta, Saul; Horta-Barba, Andrea; Kulisevsky, Jaime
ABSTRACT: Introduction : Cognitive impairment and behavioral disturbances are common findings in Parkinson's disease (PD). Despite initially being considered late complications of the disease, it is currently accepted that almost all PD patients will exhibit cognitive and behavioral abnormalities from the early and even the premotor stages of the disease. Areas covered : The present review focuses on the cognitive profile of PD, the clinical picture of PD-MCI and dementia in PD (PDD) and the recommended methods for cognitive assessment in this population. The authors also describe the more representative neuropsychiatric alterations and provide an overview of the recommended methods of assessment. Expert opinion : Cognitive and behavioral symptoms are inherent to PD, appear in a vast majority of patients at some point during disease progression and have an enormous impact on health-related quality of life of patients and caregivers. Validated methods of cognitive and behavioral assessment are currently developed and must be used in research and clinical settings.